The impact of alliance diversity on firm innovation performance: The mediating role of degree of internationalization and organizational agility, and the moderating effect of social embeddedness - Chen, Cheng; Chen, SzeTing (Edelweiss Applied Science and Technology, 2025)
This study examines how alliance diversity enhances firm innovation performance through the mediating roles of internationalization and organizational agility, with social embeddedness as a key moderator. Drawing on dynamic capabilities and social capital theories, we investigate these relationships in China’s high-tech sector using a sample of 570 firms. The research employs structural equation modeling (SEM) to analyze survey data collected through stratified random sampling. Findings reveal that both functional and technological alliance diversity significantly improve innovation performance, while internationalization and organizational agility serve as complementary mediators. Notably, social embeddedness amplifies these effects, particularly for alliance diversity. The study contributes to innovation literature by demonstrating how diverse alliances, when coupled with international exposure and adaptive capabilities, create synergistic innovation benefits, with social capital serving as a critical enabler. Practical implications suggest that managers should cultivate diverse alliance portfolios while strengthening organizational agility and social networks to maximize innovation outcomes. The research advances theoretical understanding by integrating alliance, internationalization, and agility perspectives into a unified framework, offering insights for firms navigating complex innovation ecosystems.